Lire Braudel : ouvrage collectif - Aymard, Maurice; Caillé, Alain; Dosse, François; Fourquet, François; Lacoste, Yves; Morineau, Michel; Steiner, Philippe; Wallerstein, Immanuel (Paris: La Découverte, 1988)
"par Mauric Aymard, Alain Caillé, François Dosse, François Fourquet, Yves Lacoste, Michel Morineau, Philippe Steiner, Immanuel Wallerstein Bibliotheek François Vercammen"